RESPON FISIOLOGIS AYAM JANTAN TIPE MEDIUM YANG DIBERI RANSUM DENGAN KADAR SERAT KASAR BERBEDA - Retno Dwi Sundari; Erwanto ,; Purnama Edy Santosa (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
The objective of this experiment was to find out the physiological responses of roosters medium type which were given rations in different levels of crude fiber (4, 6, 8, or 10% of dietary dry matter). This research was conducted for 60 days at cage trial installations in PT. Rama Jaya, Fajar Baru Village, Jati Agung Subdistrict, South Lampung Regency. There are fourty eight of roosters medium type that have been used and divided into 12 cages, so that each cage consisted of four roosters. The roosters were divided into four treatments. The treatment were levels of crude fiber 4, 6, 8, and 10% of dietary dry matter. Each treatment was repeated three times. The design used Completely Randomized Design (CRD) with Nested Data. Result of the experiment should that different levels of crude fiber 4, 6, 8, or 10% had no significant effect (P> 0.05) on the physiological response of rooster medium type and there was no physiological responses of the best rooster medium type in the giving of rations in levels of crude fiber 4, 6, 8, or 10%.